2016
DOI: 10.1016/j.bbalip.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

SCD1 deficiency protects mice against ethanol-induced liver injury

Abstract: Stearoyl-CoA desaturase 1 (SCD1) is a delta-9 fatty acid desaturase that catalyzes the synthesis of mono-unsaturated fatty acids (MUFA). SCD1 is a critical control point regulating hepatic lipid synthesis and β-oxidation. Scd1 KO mice are resistant to the development of diet-induced non-alcoholic fatty liver disease (NAFLD). Using a chronic-binge protocol of ethanol-mediated liver injury, we aimed to determine if these KO mice are also resistant to the development of alcoholic fatty liver disease (AFLD). Mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…During the 8-week feeding period, whereas food intake was similar in all groups, a significant decrease in body weight was observed in both EtOH-fed WT and Pxr-null mice, compared with their respective controls (Table 1) and consistent with what was observed by others (46). However, liver weight and liver-to-body weight ratios were not significantly different between the control and EtOH-fed groups of both genotypes (Table 1).…”
Section: Etoh Induces Lipid Accumulation In Wt But Not Pxr-null Micesupporting
confidence: 88%
“…During the 8-week feeding period, whereas food intake was similar in all groups, a significant decrease in body weight was observed in both EtOH-fed WT and Pxr-null mice, compared with their respective controls (Table 1) and consistent with what was observed by others (46). However, liver weight and liver-to-body weight ratios were not significantly different between the control and EtOH-fed groups of both genotypes (Table 1).…”
Section: Etoh Induces Lipid Accumulation In Wt But Not Pxr-null Micesupporting
confidence: 88%
“…Promotion of the synthesis of monounsaturated fatty acids could play an important role in the development of steatosis and liver injury with chronic-plus-binge alcohol exposure [95]. Study on SCD1 knockout mice showed significant resistance to alcohol-induced hepatic inflammation in comparison to the control group, emphasizing the critical role of SCD1 in AH [52]. SCD1 activity can be measured indirectly by the palmitoleic acid to palmitic acid ratio via serum lipid measurements [52,96].…”
Section: Stearoyl-coa Desaturase 1 (Scd1)mentioning
confidence: 99%
“…Study on SCD1 knockout mice showed significant resistance to alcohol-induced hepatic inflammation in comparison to the control group, emphasizing the critical role of SCD1 in AH [52]. SCD1 activity can be measured indirectly by the palmitoleic acid to palmitic acid ratio via serum lipid measurements [52,96]. SCD1 remains as a possible therapeutic target that needs more clinical and translational investigations to elucidate its role in inhibiting the hepatic inflammation.…”
Section: Stearoyl-coa Desaturase 1 (Scd1)mentioning
confidence: 99%
“…Stearoyl-CoA desaturase-1 (SCD1) is a delta-9 fatty acid desaturase that promotes the synthesis of mono-unsaturated fatty acids and has been found to play an important role in the development of steatosis and liver injury induced by chronic-plus-binge ethanol feeding 77 . Carboxylesterase 1 (CES1), a drug-metabolizing enzyme, has been shown to play an important role in the control of lipid metabolism 78 .…”
Section: New Insights Into the Underlying Mechanisms Of Chronic-plus-mentioning
confidence: 99%